Structure and properties of type-II clathrate Cs8Na16−xTlxGe1361. Issue 38 (14th October 2015) - Zhang, Hui; Li, Wei; Xu, Xuguang; Mu, Gang; Xie, Xiaoming; Huang, Fuqiang
<x xml:space="preserve">Abstract</x> The type-II clathrate of Cs8Na16−xTlxGe136 was synthesized.